Accents of english - Wells, J. C. (Cambridge : Cambridge University Press, 1982)
Side 1. Examples 1-8 -- Side 2. Examples 9-20
1. An introduction -- 2. The British Isles -- 3. Beyond the Bristish Isles
Keywords: INGLÉS; LENGUAJE; DIALECTOLOGIA; FONOLOGIA; GRABACIONES SONORAS